Daur Hidup Masyarakat Bumi Lale Di Pulau Buru - Kubangun, Nur Aida (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
The Bumi Lale community is unique and is commonly referred to by the coastal communities on the island of Buru as the hindquarters. They have traditional ceremonies by the life cycle and natural phenomena. This traditional ceremony is carried out from generation to generation. This life cycle ceremony's purpose is safety, which symbolizes good hope and moral education as local wisdom rooted in past socio-cultural thoughts and senses. This article discusses the life cycle of the Bumi Lale people, which is one of the myths in their cultural life and is very much believed by the community; if they do not perform ceremonies in each life cycle, it will bring danger to their village. The life cycle starts with pregnancy, birth, marriage and death.